Sustainable management of land resources in the context of agricultural policy in the Republic of Moldova - Tamara Leah (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Natural and anthropogenic conditions determine the intensity and direction of pedogenesis, as well as the nature and degree of degradation of the soil cover of the Republic of Moldova. Depending on the combination of natural and anthropogenic factors, the forms of land degradation are expand. The main natural factors of land degradation are: quaternary deposits, represented by loess clay, ancient and modern alluvial deposits of different granulometric compositions, from clays to sands; parental rocks; the presence of seven orographic units in a restricted area. The most common exogenous processes leading to land degradation are: erosion, landslide, proluvio-deluvial, avalanche, fusion and karst process. The evolution of the balance of organic matter in arable soils became negative. In a period of 150 years, the chernozems lost up to 50% of their initial humus content. The annual losses of organic matter through decomposition are on average 600-700 kg/ha, in the last 20 years - 900 kg/ha. The torrential nature of the precipitation in the conditions of a fragmented relief contributes to the intensive development of land erosion and the manifestation of different forms of soil degradation. The arid character of the climate, the frequent dry periods (droughts), the predisposition of the territory to the manifestation of desertification processes, require the adaptation of agriculture to these conditions.
Keywords: Q1; Q15; 330; land degradation; land resources; sustainable management; agricultural policy